Quinolizidine alkaloid profiles of two taxa of Teline maderensis - Martins, Alice; Wink, Michael; Tei, Andreas (Zeitschrift für Naturforschung. C, a journal of biosciences, 2014)
The alkaloid composition of the aerial parts of two taxa of Teline maderensis was studied by capillary GLC and GLC-MS. N-Methylcytisine was the major alkaloid found in both plants. Contents of cytisine and lupanine were higher in T. maderensis var. paivae while anagyrine content was more pronounced in T. maderensis var. maderensis. The alkaloids dehydrocytisine, N-acetylcytisine and epibaptifoline appeared only in T. maderensis var. maderensis and N-formylcytisine was identified as a minor constituent in T. maderensis var. paivae, and detected only in trace amounts in the other variety of the plant.
Gesehen am 04.10.2017